2017
DOI: 10.1080/1028415x.2017.1354959
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of raisin (currant) against spatial memory impairment and oxidative stress in Alzheimer disease model

Abstract: Our findings showed that raisin has a neuroprotective effect and improves the spatial memory in AD animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…MDA and SOD can be used as markers of oxidative stress; the former can indirectly represent the formation and scavenging of oxygen free radicals, and the latter can protect organisms from oxidative stress damage. [17,18] In addition, our study found oxidative stress and inflammation in asymptomatic young patients with primary hyperuricemia.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…MDA and SOD can be used as markers of oxidative stress; the former can indirectly represent the formation and scavenging of oxygen free radicals, and the latter can protect organisms from oxidative stress damage. [17,18] In addition, our study found oxidative stress and inflammation in asymptomatic young patients with primary hyperuricemia.…”
Section: Discussionmentioning
confidence: 50%
“…MDA is the product of the oxygen radical chain reaction in organisms and can indirectly represent the formation and scavenging of oxygen free radicals in organisms. [17] SOD is an important antioxidant substance in organism and can increase the activity of antioxidant enzymes and eliminate oxygen radicals produced by internal metabolism [18] to protect organisms from oxidative stress damage. In our study, we aimed to explore the oxidative stress and inflammation in patients with hyperuricemia.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the ability of tannins and tannin-containing natural products to ameliorate memory impairment in various model animals with AD-like phenotypes. The treatment of some tannins (including corilagin, punicalagin, and raisin) ameliorated the memory impairment in radiation-induced brain injury (RIBI), LPS-induced neuroinflammation resulting in memory impairment, and aluminum chloride injected model [30,31,32]. Similar memory enhancing effects were induced after treatment with tannin-containing natural products.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Gol et al. 2017). Therefore, it is concluded that the neuroprotective nature of D. aucheri extract in pre-treated ischaemic rats may be related to the mentioned constituents during cerebral ischaemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%